The effects of brodifacoum cereal bait pellets on early life stages of the rice coral Montipora capitata - Barkman, Alexandria L.; Richmond, Robert H. (PeerJ, 2022)
Midway Atoll in the Northwestern Hawaiian Islands is home to ground nesting birds that are threatened by invasive mice. Planned rodent eradication efforts for the island involve aerial application of cereal bait pellets containing the chemical rodenticide brodifacoum. Given the nature of the application method, drift of cereal bait pellets into the coastal waters surrounding Midway Atoll is unavoidable. To understand whether cereal bait pellets impact marine invertebrates, gametes and larvae of the reef-building coral Montipora capitata were exposed to brodifacoum, cereal bait pellets containing brodifacoum, and inert cereal bait pellets without the rodenticide. Fertilization success and larval survival were assessed at nominal brodifacoum concentrations of 1, 10, and 100 ppb. Fertilization success decreased by 15% after exposure to 100 ppb brodifacoum solutions. Larval survival was not reduced by exposure to brodifacoum solutions. Cereal bait pellets containing brodifacoum reduced fertilization success at 10 ppb brodifacoum in 0.4 g per L pellet solutions by 34.84%, and inhibited fertilization at 100 ppb brodifacoum in 4 g of pellet per L solution. Inert cereal bait pellets had similar effects, reducing fertilization success at 0.4 g of pellet per L by 40.50%, and inhibiting fertilization at 4 g per L pellet solutions. Larval survival was reduced by >43% after prolonged exposure to 4 g per L pellet solutions. The highest concentration used in this study was meant to represent an extreme and unlikely condition resulting from an accidental spill. Our findings indicate large amounts of cereal bait pellets entering the coastal environment of Midway Atoll, if occurring during a coral spawning event, would reduce coral reproduction by decreasing fertilization success. It is difficult to know the ecologically relevant concentrations of cereal bait pellets in coastal environments due to unavoidable bait drift after land applications, but results indicate small amounts of pellet drifting into coastal environments would not severely reduce coral reproductive capacity. Best management practices should consider known coral reproductive periods when scheduling applications of pellets on tropical islands to reduce the risk of negative impacts of large-scale accidents on corals.
Keywords: Coral reproduction; Pesticides; Brodifacoum; Rodent eradication